Interpersonal Communication of Matchmaking Shamans - Ita Rahmawati; Moch. Sheva Indraputra; Nurfitroh Rahmawati; Detya Wiryany (Westscience Press, 2023)
This research is based on the interpersonal communication approach method between the shaman and the patient. The methodology used also uses descriptive qualitative with the aim of understanding the communication used by shamans in general. The subjects of this study were traditional healers and patients in the Bandung Regency area. Data collection techniques through observation and interviews. Researchers use the theory of Symbolic Interaction. The conclusion of this study is that the visible influence on the surrounding community is due to the communication skills possessed by the shaman. The interpersonal communication possessed by the shaman can influence a patient to express the problems he is experiencing, such as matters of mate. The shaman has the ability to help a person find his life partner through spiritual methods or expertise, this makes people believe in shamans more.